2020
DOI: 10.26717/bjstr.2020.28.004714
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Soil on Some Heavy Metals and its Pollution in Roodsar-Iran

Abstract: Increased concentrations of heavy metals in the air, soil, or water threatens human health both directly and indirectly via accumulation in the food chain. In countries with high ecological awareness the risk of acute exposure has been minimized thanks to the enforcement of restoration laws and policies. This paper presents results of chemical analysis of soil samples to total content of Pb, Ni, Cr and Cu. Samples were collected at site of Roodsar, at two depths in November 2019th year. These heavy metals were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…A relevant aspect that should be considered is that during the cultivation and development of medicinal plants, they could have been contaminated with heavy metals because they may have been irrigated for long periods of time with untreated water or wastewater or growing in areas of intense traffic or near areas of industrial waste. For example, several studies have been conducted in Asia that clearly showed soil contamination by heavy metals on roadsides with different volumes of traffic [ 50 , 51 ]. These soils may subsequently be used for agricultural practices and enter the food chain.…”
Section: Discussionmentioning
confidence: 99%
“…A relevant aspect that should be considered is that during the cultivation and development of medicinal plants, they could have been contaminated with heavy metals because they may have been irrigated for long periods of time with untreated water or wastewater or growing in areas of intense traffic or near areas of industrial waste. For example, several studies have been conducted in Asia that clearly showed soil contamination by heavy metals on roadsides with different volumes of traffic [ 50 , 51 ]. These soils may subsequently be used for agricultural practices and enter the food chain.…”
Section: Discussionmentioning
confidence: 99%
“…In order to promote community health and eliminate the exorbitant costs of treatment, it is enough to create a proper culture about these products so that communities are encouraged to use these natural medicines and do not start using chemical medicines with any small disease. For example, the common cold or common new weak mutations of Covid 19 are some of the diseases that people get several times a year, if you are careful, people who constantly take a variety of pills to cure this disease (even before the disease and with the least symptoms to try), they take more colds than other people for a long time, but people who are more resistant and use less pills and chemicals have a stronger immune system and last longer [52][53][54][55][56][57][58]. They achieve a short recovery time.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above explanations, the use of natural compounds for other diseases related to chronic inflammation such as arteriosclerosis and ischemia has been found to be useful and effective. [19][20][21][22][23] The present research provides important results regarding the therapeutic or preventive effects of natural compounds in chronic inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%